Five things you wanted to know about audiovisual translation research, but were afraid to ask - Szarkowska, Agnieszka; Wasylczyk, Piotr (Journal of Audiovisual Translation, 2018)
Young researchers often encounter questions, problems and hurdles at the early stages of their careers that relate to areas, particularly outside their core subject. These may span from selecting the research topic and methodology to publishing strategies and identifying the position of audiovisual translation research in a wider framework of the fast-changing academic world. Drawing on our experience in audiovisual translation and natural sciences research, we address some of these issues in a way we wish someone had done for us many years ago.